Influence of the Board of Directors, Financial Distress, and Tax Risk Management on Tax Avoidance with Capital Intensity as Moderation - Jelena Jelena; Budi Chandra (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2022)
ABSTRACT This research was conducted to determine the number of companies listed on the IDX that had been carried out and the effects presented in the application of tax avoidance. From the study results, there are variables of board gender diversity, board diligence, and board size that have no significant effect, and variables of financial distress and tax risk management bring significant influences between the dependent and independent variables, which are supported by moderating variables. So, the result suggests that companies implementing tax risk management can affect tax avoidance. ABSTRAK Penelitian bertujuan untuk mengetahui dan menganalisis dampak yang ditimbulkan oleh penerapan penghindaran pajak. Dari hasil penelitian, terdapat variabel board gender diversity, board diligence, dan board size yang tidak berpengaruh signifikan, serta variabel financial distress dan tax risk management berpengaruh signifikan antara variabel dependen dan independen yang didukung oleh variabel moderasi. Hasil penelitian menunjukkan bahwa perusahaan yang menerapkan manajemen risiko pajak dapat mempengaruhi penghindaran pajak.